2021
DOI: 10.3346/jkms.2021.36.e278
|View full text |Cite
|
Sign up to set email alerts
|

Severe Disease Activity Based on the Paris Classification Is Associated with the Development of Extraintestinal Manifestations in Korean Children and Adolescents with Ulcerative Colitis

Abstract: Background There are limited data regarding the extraintestinal manifestations (EIMs) associated with pediatric inflammatory bowel disease (IBD) in Korea. We aimed to investigate the clinical features and factors associated with the development of EIMs in Korean children and adolescents with IBD. Methods This multicenter, retrospective study was conducted from 2010 to 2017. Baseline clinicodemographic, laboratory findings, disease activity, disease phenotypes, and EIMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, contrary to these findings, PUCAI and PCDAI scores at diagnosis did not differ significantly between EIM-positive and EIM-negative patients. [10] Regression analysis also revealed no significant relationship between the development of EIM and PUCAI. [10] Yu et al [6] found a relationship between the severity of the disease at diagnosis and the development of EIM.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, contrary to these findings, PUCAI and PCDAI scores at diagnosis did not differ significantly between EIM-positive and EIM-negative patients. [10] Regression analysis also revealed no significant relationship between the development of EIM and PUCAI. [10] Yu et al [6] found a relationship between the severity of the disease at diagnosis and the development of EIM.…”
Section: Discussionmentioning
confidence: 94%
“…It was found to be the most common EIM joint finding (arthritis) in IBD patients (12-21%). [6,10,12,13,16,17] In a study designed by Rahmani et al [12] in CD and UC patient groups, the incidence of EIM related with joint was found to be 21.2% and 12.5%, respectively. Oral aphtha was seen in 15% of CD patients, but not in UC patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 1 Once IBD is diagnosed in children, the goals of therapy consist of eliminating symptoms, normalizing quality of life, restoring growth, and preventing complications while minimizing the adverse effects of medications. 1 2 In addition, pediatric IBD has a more aggressive disease course than adult-onset disease. Therefore, early introduction of immunomodulators including anti-tumor necrosis factor (TNF) agents is required.…”
Section: Introductionmentioning
confidence: 99%